2018
DOI: 10.1186/s12934-018-0926-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cellulase production in Trichoderma reesei RUT C30 via constitution of minimal transcriptional activators

Abstract: BackgroundCellulase can convert lignocellulosic feedstocks into fermentable sugars, which can be used for the industrial production of biofuels and chemicals. The high cost of cellulase production remains a challenge for lignocellulose breakdown. Trichoderma reesei RUT C30 serves as a well-known industrial workhorse for cellulase production. Therefore, the enhancement of cellulase production by T. reesei RUT C30 is of great importance.ResultsTwo sets of novel minimal transcriptional activators (DBDace2-VP16 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Thus, several attempts were made to alleviate CCR by introducing modifications in Cre1 for improving cellulase production. It was proved that replacement of the endogenous transcription factor Cre1/CreA by an artificial minimal transcriptional activator, such as Cre1-96 or other Cre1/CreA mutants, leads to release or attenuation of CCR, which in turn is supports cellulase production efficiency in T. reesei or A. nidulans (Shroff et al, 1997;Mello-de-Sousa et al, 2014;Rassinger et al, 2018;Zhang et al, 2018). However, Liu et al (2019) demonstrated that full-length Cre1 might be necessary for the rapid growth of T. reesei.…”
Section: Figmentioning
confidence: 99%
“…Thus, several attempts were made to alleviate CCR by introducing modifications in Cre1 for improving cellulase production. It was proved that replacement of the endogenous transcription factor Cre1/CreA by an artificial minimal transcriptional activator, such as Cre1-96 or other Cre1/CreA mutants, leads to release or attenuation of CCR, which in turn is supports cellulase production efficiency in T. reesei or A. nidulans (Shroff et al, 1997;Mello-de-Sousa et al, 2014;Rassinger et al, 2018;Zhang et al, 2018). However, Liu et al (2019) demonstrated that full-length Cre1 might be necessary for the rapid growth of T. reesei.…”
Section: Figmentioning
confidence: 99%
“…Cellulase production by the mono and co-culture For the mono-culture, T. asperellum (TA) (10 6 /mL spores) or the recombinant T. asperellum (TA OE-Vel1) (10 6 /mL spores) were cultured in the minimal broth containing 2% avicel as described by [35]. For co-cultivation, 0.1% of the B. amyloliquefaciens 1841 (BA) was added into the 48 th hour T. asperellum and recombinant T. asperellum pre-culture medium and named as TA+BA and TA OE-Vel1+BA respectively.…”
Section: Engineering Of Vel1 Gene Overexpressionmentioning
confidence: 99%
“…The endoglucanase (CMCase) activity was tested according to Bailey and Nevalainen [37]. Cellobiohydrolase (pNPCase), and β-glucosidase (pNPGase) were assessed by the methodology of Zhang et al [35]. Xylanase I and II were assessed at pH 3.7 and 5.0 respectively according to the method of Sticker et al [38].…”
Section: Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, artificial transcription factors (ATFs) have also been studied to genetically engineer cellulase production. For example, the repressor Cre1 could be changed to transcriptional activator for cellulases gene expression by replacement of the VP 16 activation domain (AD) (Zhang J. et al, 2018). In the previous studies, a library of artificial zinc finger proteins (AZFPs) was explored for expression in bacteria and yeast (Park et al, 2003;Ma et al, 2015), and screened for mutants with changed phenotypes.…”
Section: Introductionmentioning
confidence: 99%